Manipulation of Evanescent Wave Coupling in High-Q Terahertz All-Dielectric Metasurfaces - Song Han (IEEE Photonics Journal, 2023)
The resonance characteristics in periodically arranged artificial dielectric photonics and metasurfaces have attracted interests due to their growing applications in filters, low-threshold lasers, nonlinear generation of light, waveguides, chemical and biological sensors. Here, we experimentally demonstrate a family of silicon-based terahertz metasurfaces supporting high-Q resonances that is illustrated theoretically by the extended Marcatili's analysis in periodic boundary condition. We further reveal that the evanescent wave coupling along the direction of incident electric field merely radiate EM energy. Therefore, the vary of geometric parameter along such direction mainly change the resonance frequencies of the cuboid-based dielectric metasurface, while the resonant amplitudes and Q-factors at different geometric parameters are almost the same. Such characteristics is highly promising for application of on-chip THz/mid-IR spectrometer by spatially arranging different cuboid-based dielectric metasurfaces with scaled dimensions. The extended Marcatili's analysis shown here could further enable design of flat nanoscale metasurfaces for optical applications.